Granisetron plus aprepitant versus granisetron in preventing nausea and vomiting during CHOP or R-CHOP regimen in malignant lymphoma: a retrospective study - Yoshinori Wakasugi; Satoshi Noda; Yoshihiro Ikuno; Miya Horie; Katsuyuki Kito; Hitoshi Minamiguchi; Tomohiro Terada (BMC, 2019)
Abstract Background Cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP) regimen includes a high dose of prednisolone (100 mg/body), which exhibits an anticancer and antiemetic effect. However, its optimal use for antiemetic therapy has not been established yet. We assessed the efficacy of granisetron plus aprepitant versus granisetron for CHOP or rituximab-CHOP (R-CHOP) regimen-induced nausea and vomiting in malignant lymphoma. Methods This retrospective and observational clinical study included patients who received CHOP or R-CHOP regimen as initiating chemotherapy between July 2010 and March 2016 (N = 39). Patients were assigned to an aprepitant [aprepitant (125 mg on day 1, 80 mg on days 2-3) plus granisetron (3 mg); n = 15] or control regimen group [granisetron (3 mg); n = 24]. Complete response (CR), defined as no vomiting and no use of rescue therapy during overall phase (0-120 h), was the primary endpoint. Secondary endpoints included the time to first vomiting and using rescue medication and complete protection (CP) defined as no vomiting and no retching and/or no nausea and no rescue therapy. The patient records were investigated, and data were retrospectively analyzed. Results CR rate CP rates did not significantly differ between the groups during the observation period (80.0% versus 83.3%, p = 1.000; and 80.0% versus 79.2%, p = 1.000, respectively). Additionally, the time to first vomiting and using rescue medication in did not significantly differ between the groups (p = 0.909). Conclusions This study suggests that granisetron alone could be one treatment option in the management of CINV in patients with non-Hodgkin lymphoma receiving CHOP or R-CHOP regimen.